The Synergistic Effect of Mud Crab Antimicrobial Peptides Sphistin and Sph12−38 With Antibiotics Azithromycin and Rifampicin Enhances Bactericidal Activity Against Pseudomonas Aeruginosa - Liu, Jie; Chen, Fangyi; Wang, Xiaofei; Peng, Hui; Zhang, Hua; Wang, Ke-Jian (Frontiers in Cellular and Infection Microbiology, 2020)
Overuse or abuse of antibiotics has undoubtedly accelerated the increasing prevalence of global antibiotic resistance crisis, and thus, people have been trying to explore approaches to decrease dosage of antibiotics or find new antibacterial agents for many years. Antimicrobial peptides (AMPs) are the ideal candidates that could kill pathogens and multidrug-resistant bacteria either alone or in combination with conventional antibiotics. In the study, the antimicrobial efficacy of mud crab Scylla paramamosain AMPs Sphistin and Sph12−38 in combination with eight selected antibiotics was evaluated using a clinical pathogen, Pseudomonas aeruginosa. It was interesting to note that the in vitro combination of rifampicin and azithromycin with Sphistin and Sph12−38 showed significant synergistic activity against P. aeruginosa. Moreover, an in vivo study was carried out using a mouse model challenged with P. aeruginosa, and the result showed that the combination of Sph12−38 with either rifampicin or azithromycin could significantly promote the healing of wounds and had the healing time shortened to 4–5 days compared with 7–8 days in control. The underlying mechanism might be due to the binding of Sphistin and Sph12−38 with P. aeruginosa lipopolysaccharides (LPS) and subsequent promotion of the intracellular uptake of rifampicin and azithromycin. Taken together, the significant synergistic antibacterial effect on P. aeruginosa in vitro and in vivo conferred by the combination of low dose of Sphistin and Sph12−38 with low dose of rifampicin and azithromycin would be beneficial for the control of antibiotic resistance and effective treatment of P. aeruginosa-infected diseases in the future.